Strategic framing of novel ideas: How contestation shapes the evolution of novelty - Klein, Janina; van Burg, Elco; Moser, Christine (Strategic Entrepreneurship Journal, 2026)
Abstract Research Summary Entrepreneurs use strategic framing to gain support for their novel ventures, products, and services. A key challenge entrepreneurs face is that audiences often contest frames that introduce novel ideas, especially when these ideas disrupt audiences' mental and business models. Such contestation can hinder novel ideas from being accepted, a risk that is amplified when entrepreneurs face contestation from multiple audiences. We lack understanding, however, of how contestation from multiple audiences shapes the strategic framing of novel ideas. We study this question at Tony's Chocolonely, a social enterprise that faced such contestation when introducing “slave‐free” chocolate. By showing how the social enterprise reacted to contestation from multiple audiences in different ways, we uncover novel mechanisms of frame change and stability. Managerial Summary Entrepreneurs use strategic framing to gain support for their novel ideas, products, and services. In so doing, they must navigate resistance from different audiences, especially when entrepreneurs introduce novel ideas that disrupt the status quo. Audience resistance can hinder novel ideas from gaining momentum. We do not know, however, how entrepreneurs can navigate resistance from multiple audiences. Our study examines how Tony's Chocolonely, a social enterprise fighting child labor in the chocolate industry, navigated resistance against its “slave‐free” chocolate from diverse audiences. Our study reveals novel insights into how audience resistance shapes entrepreneurs' strategic framing of novel ideas.